The Synergistic Antifungal Effect and Potential Mechanism of D-Penicillamine Combined With Fluconazole Against Candida albicans - Li, Yiman; Jiao, Ping; Li, Yuanyuan; Gong, Ying; Chen, Xueqi; Sun, Shujuan (Frontiers in Microbiology, 2019)
Over the last few decades, candidiasis has exhibited an increasing incidence worldwide, causing high mortality in immunocompromised patients. Candida albicans is one of the leading opportunistic fungal pathogens. However, due to the increased use of antifungal agents, resistance of Candida albicans to conventional agents, especially fluconazole, has frequently emerged. Therefore, research on the use of combinations of current drugs to sensitize antifungal agents and overcome fungal resistance has attracted considerable attention. This study demonstrated for the first time that D-penicillamine combined with fluconazole showed a synergistic effect against Candida albicans. D-penicillamine combined with fluconazole not only showed synergistic effects against planktonic cells of Candida albicans but also showed synergistic effects against Candida albicans biofilms formed within 12 hours in vitro. In addition, a Galleria mellonella infection model was used to evaluate the in vivo effects of this drug combination. The results showed that the combination of the two drugs could improve the survival rate and decrease the fungal burden of Galleria mellonella larvae. Finally, we explored the potential synergistic mechanisms of the drug combination, mainly including inhibition of the morphological transformation, reduction of the intracellular calcium concentration and the activation of metacaspase, which is closely related to cell apoptosis. These findings might provide novel insights into antifungal drug discovery and the treatment of candidiasis caused by Candida albicans.